Upaya Meningkatkan Pembelajaran Passing Pendek Melalui Permainan Futsal Mengunakan Target Pada Siswa Kelas IV Di SD Global Prima - Tuti Alawiyah, Abdullah Safei; Ridlo, Azi Faiz; Abidin, Dindin (Motion: Journal Research of Physical Education, 2025)
This study uses the Classroom Action Research (CAR) method, in its implementation consisting of two cycles. Each cycle is carried out 4 times and consists of four stages, namely: planning, implementation, observation, and reflection. The subjects of this study were 20 fourth grade students at SD Global Prima in the 2024/2025 academic year, consisting of all male students. The instruments used in this study were performance, tests, and observation sheets. In the initial observation, students before the first action test or cycle I got a very good score of 0%; good 15%; enough 15%; less 50%; and very less 20%;. And in the cycle I test, they got a very good score of 10%; good 25%; enough 30%; less 30%; and very less 5%. An increase occurred in the cycle II test, getting a very good score of 20%; good 45%; enough 25%; less 10%; and very less 0%. Based on the results of the study above, it can be concluded that there is an increase in the learning outcomes of Short Passing futsal game of grade IV students at SD Global Prima in the academic year 2024/2025. Basic short passing skills can be developed in futsal games to higher levels. For teachers in learning games using big balls, especially futsal games, it is hoped that they can develop other more interesting skill game models to be used in learning game modifications at school.